Analisis Pengaruh Harga, Pendapatan, dan Bandwagon Effect Terhadap Permintaan Tiket Konser K-Pop: Studi Kasus Konser the Dream Show 4 in Jakarta - Kayla Herdani Arminta; Dicky Iranto; Fitra Dila Lestari (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This quantitative correlational study with a cross-sectional approach analyzes the phenomenon of high demand for K-Pop concert tickets in Jakarta despite financial barriers such as price spikes and limited income. Conducted from June 11 to 13, 2026, the study aims to examine the relationships among variables within the NCTzen population, which constitutes the target market for the Dream Show 4 concert in Jakarta. The sample was determined using “purposive sampling”; primary data was collected via an online questionnaire, while secondary data was obtained from official publications by the BPS, and news media. All respondents were women of working age in the Greater Jakarta area employed as lower-middle-class workers. Data analysis utilized descriptive statistics, instrument validation, and tests of classical assumptions. The results of the descriptive analysis revealed that the influence of the Bandwagon Effect was classified as low, while the level of ticket demand fell into the high category. This study concludes that price has a significant and direct effect on demand due to the Veblen Effect. Conversely, the income variable and the Bandwagon Effect do not have a significant impact. Ticket-purchasing decisions are driven by strong individual internal motivations for social status rather than environmental trends or income levels.